1997
DOI: 10.1080/10934529709376582
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine residues in normal and lead poisoned greater flamingos: Relationships with the fatty acid composition

Abstract: Livers from 65 greater flamingos [Phoenicopterus ruber roseus) collected in three Spanish wetlands were analyzed for organochlorine (OC) residues and fatty acid (FA) composition. Some of these birds were lead poisoned (n=52), as determined in a previous study published elsewhere. The effects of OC levels and normal/abnormal lead levels on the FA composition were analyzed with ANOVA tests in order to establish possible influences among them. High lead concentration was found to increase the relative proportions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
1
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
0
1
2
Order By: Relevance
“…Years later, Zapata et al (2018), found mean concentrations of ∑ PCBs ranging from 0.11 to 253 ng/g (ww) and ∑ DDTs from 0.05 to 218 ng/g (ww) in eggs of Larus michahellis, as well as ∑ PCBs ranging from 0.20 to 304 ng/g (ww) and ∑ DDTs from 0.02 to 760 ng/g (ww) in eggs of Larus audouinii. A monitoring study conducted on flamingos from Ebro Delta Natural Park reported higher concentrations of organochlorine pesticides (DDTs, HCBD and HCHs) in livers than those reported in blood in the present study (Gutiérrez et al, 1997). Differences in concentrations among matrices are due to the higher lipid content of livers, enhancing the accumulation of persistent compounds such as DDTs and PCBs compared to blood (Espín et al, 2016).…”
Section: Oc Pesticides and Pcbscontrasting
confidence: 51%
“…Years later, Zapata et al (2018), found mean concentrations of ∑ PCBs ranging from 0.11 to 253 ng/g (ww) and ∑ DDTs from 0.05 to 218 ng/g (ww) in eggs of Larus michahellis, as well as ∑ PCBs ranging from 0.20 to 304 ng/g (ww) and ∑ DDTs from 0.02 to 760 ng/g (ww) in eggs of Larus audouinii. A monitoring study conducted on flamingos from Ebro Delta Natural Park reported higher concentrations of organochlorine pesticides (DDTs, HCBD and HCHs) in livers than those reported in blood in the present study (Gutiérrez et al, 1997). Differences in concentrations among matrices are due to the higher lipid content of livers, enhancing the accumulation of persistent compounds such as DDTs and PCBs compared to blood (Espín et al, 2016).…”
Section: Oc Pesticides and Pcbscontrasting
confidence: 51%
“…Dentro de los HCHs, Nisbet (1975) observó que el lindano afecta a la reproducción de las aves. Gutiérrez et al (1997) encontraron HCHs en el hígado de flamencos del Parque Natural de Santa Pola y en el Delta del Ebro.…”
Section: Hchsunclassified
“…Hay también evidencia de mortalidad en aves adultas y embriones después de tratamiento con DDD en Clar Lake (California) (Fry, 1995). Se informó de la predominancia del DDE en el hígado (Gutiérrez et al, 1997) y huevos (Hernández et al, 1984) de flamencos en la Península Ibérica. En el estudio de Guitart et al (2005), el valor medio de DDE en los huevos de flamenco fue de 1.503 mg/kg.…”
Section: Ddtsunclassified